Pendidikan Islam Kurikulum Bersepadu Sekolah Menengah (KBSM): Satu Analisis dari Perspektif Pendidikan Luqman - Ahmad, Abdul Rashid (Jurnal Usuluddin, 1996)
The study is an attempt to analyse the content of the syllabus of Islamic Education of the currently practised integrated secondary school curriculum (KBSM) in the perspective of the method of Luqmans teaching his children as mentioned in the Quran of which the main contents were aqidah, ibadah and akhlak. The study confirms that the syllabus bears the contents of Luqman's teaching as well as covering some other aspects history, civilisation, economy and Islamic Law and society in accordance with its aim of creating an ethical and hardworking young generation in facing the challenges of the future.